The Inundation Signatures on Rocky Coastlines Global Database for coastal boulder deposits (ISROC-DB) - Kennedy, Andrew; Cox, Rónadh; Engel, Max; Speyrer, Emma; Lau, Annie; Mori, Nobuhito (Marine geology, 2025)
Coastal boulder deposits are long-lived signatures of high-energy storm wave and tsunami inundation found on rocky and reefal coastlines worldwide. Although increasing numbers of research reports have been published on coastal boulder deposits, it has been difficult to compare studies from different areas because of a lack of standardised data and of quality-controlled datasets. This paper describes ISROC-DB, a new standardised database compiled from both published and unpublished data. There are two important parts: 1. Uniform standards to enable collation and intercomparison of coastal boulder deposits, with preformatted Excel files to enable convenient data entry; and 2. A freely accessible compiled database of coastal boulder deposit data. Both are published in downloadable permanent archives. Ongoing additions will further increase the database scope.
Online verfügbar: 16. Mai 2025, Artikelversion: 17. Mai 2025
Gesehen am 14.08.2025